Mitigation of Cryopreservation Induced Changes in Murrah Buffalo (Bubalus bubalis) spermatozoa using L-Cysteine Hydrochloride - Alam, Kabir; Srivastava, Sushant; Jaiswal, Ankit; Kumar, Rajesh; Verma, Abhishek Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
This investigation was carried out with the objective of finding improvements in the quality of frozen semen from buffalo bulls with the  incorporation of cysteine as an additive in tris dilutor. Thirty-six ejaculates from six Murrah buffalo bulls of 6-8 years of age group were  collected in sterilized artificial vagina to evaluate the effect of additives at the post-dilution and post-thaw stages. The semen sample  was extended with Tris-Citric-acid-Fructose-Egg-Yolk--Glycerol (TFYG) extender and was divided into two groups: Group I without any  additive served as control (C) group, while Group II, extender supplemented with L-cysteine hydrochloride (1.0 mM) served as treatment  (T) group. Progressive sperm motility, live spermatozoa, sperm abnormalities, and enzyme leakage (AST and ALT) were evaluated at both  post-dilution and post-thaw stages. There was significant (p
Keywords: Additives; Cryopreservation; L-cysteine hydrochloride; Murrah semen